1977
DOI: 10.1063/1.861773
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Schrödinger equation including growth and damping

Abstract: The nonlinear Schrödinger equation, with complex coefficients that describe growth and damping, is considered. An exact stationary soliton solution is found for arbitrary growth and damping strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(128 citation statements)
references
References 12 publications
1
127
0
Order By: Relevance
“…To this end, we consider a complex Ginzburg-Landau model with the cubic nonlinearity (CGL3), for which an analytical chirped-sech localized solution is well known in the one-dimensional (1D) setting [10,11]. While this solution is always unstable, it has been shown that an additional, linearly coupled, dissipative linear equation can lead to its stabilization in coupled-waveguide models, keeping the solution in the exact analytical form [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we consider a complex Ginzburg-Landau model with the cubic nonlinearity (CGL3), for which an analytical chirped-sech localized solution is well known in the one-dimensional (1D) setting [10,11]. While this solution is always unstable, it has been shown that an additional, linearly coupled, dissipative linear equation can lead to its stabilization in coupled-waveguide models, keeping the solution in the exact analytical form [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…4 shows that, when operating in the BF unstable regime (i.e., we have set α = 0.6, β = 3, so that 1 − αβ < 0, ρ = −3, and γ = 0.95), it is also possible to generate a uniform and spatiotemporally stable lattice of anticorrelated (or antiphase) temporal solitons. The individual pulses in each polarization component are well matched by the exact soliton-like solution of the scalar complex GinzburgLandau equation [45], namely,…”
Section: Modeling Vector Dynamics With Coupled Ginzburg-landau Eqmentioning
confidence: 90%
“…(1) are nonlinearity and bandwidthlimited amplification, irrespective of the sign of GVD. 14,15 Neglecting at first for simplicity higher-order nonlinear gain saturation and frequency shifting, that is, with s a 0, one obtains an exact solution for Eq. (1) in the form 11,14 u A͓sech͑T͞r͔͒ 12in exp͑iGZ͒ ,…”
Section: Exact Solutionsmentioning
confidence: 99%